THE FREUDIAN PSYCHOLOGICAL PHENOMENA AND COMPLEXITY IN DAPHNE DU MAURIERâ€™S â€œREBECCAâ€ (A PSYCHOLOGICAL STUDY OF LITERATURE) - Hadiyanto Hadiyanto (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
The relationship between literature and psychology commonly derives from psychological dimension in literary works and the application of psychology theory in interpreting literary texts. This essay discusses a psychological study in Daphne Du Maurier’s Rebecca based on Sigmund Freud’s psychoanalysis theory. Rebecca is a very psychological novel, since a lot of psychological phenomena emerges from the beginning to the end of the novel. Psychological phenomena found in the novel among other things are dream analysis, Narcissist complex, Cinderella complex, Electra complex, impulsive id, ego, and super ego, cathexis, as well as various types of ego defense mechanism. Each character within the novel such as Rebecca, Maxim de Winter, Maxim’s second wife, and Mrs. Danvers, have his or her psychological characteristics, reaction, and problem. Dream in the beginning and the burning Manderley house at the end of the story are symbol of the ultimate psychological phenomena in the novel Rebecca.